Losing Genes: The Evolutionary Remodeling of Cetacea Skin - Espregueira Themudo, Gonçalo; Alves, Luís Q.; Machado, André M.; Lopes-Marques, Mónica; da Fonseca, Rute R.; Fonseca, Miguel; Ruivo, Raquel; Castro, L. Filipe C. (Frontiers in Marine Science, 2020)
The skin is a multi-layered organ, often displaying associated structures, that establishes a protective interface between the organism and the surrounding environment. In mammals, the skin provides a physical and immune barrier, while contributing to thermoregulation and water balance. Within cetaceans, the archetypal mammalian skin was drastically reshaped and remodelled, emerging as a striking feature of their successful adaptation to a fully aquatic lifestyle. In fact, cetacean skin is extremely thick, displays a high cellular turnover rate, and lacks typical mammalian pelages, as well as sebaceous glands, resulting in a smooth and drag-reducing skin. Curiously, at the genome level, the majority of cetacean skin-related innovations resulted from episodes of gene loss: spanning diverse processes such as skin keratinization and cornification, immunity and inflammation or lubrication. Here, we review how cetacean skin was shaped by such an evolutionary mechanism, by describing the full set of genes with inactivating mutations in the various functional compartments of the skin.